Research on Influencing Factor of Transmission Accuracy of Split Anti-backlash Worm Pair - Zhihong Liang; Yayin He; Kai Wang; Yongqiang Zhao (Jixie chuandong)
The split anti-backlash worm pair eliminates the worm backlash by rotating and adjusting the distance between the two worms. In view of its anti-backlash method and the structural characteristics of the existence of thinner worm teeth， the factors affecting the transmission accuracy of the split anti-backlash worm pair are studied， a 3D model and motion analysis model of split anti-backlash worm pairs are established and the influencing law of worm pair use error and worm pair structure error on the transmission accuracy of worm pairs is studied. The result shows that the use error of the worm pair has a greater impact on the transmission accuracy of the worm pair than the structural error of the worm pair does， the wear in the worm gear teeth has the greatest impact on the transmission accuracy in the use error and the radial error in the structural error has the greatest influence on the transmission accuracy.